Effect of block periodization on performance in competition in a soccer team during four consecutive seasons: A case study - Mallo, J. (International Journal of Performance Analysis in Sport, 2011)
The purpose of this study was to examine the effect of applying block periodization on performance in competition in a Spanish professional soccer team during four consecutive seasons. A longitudinal training protocol was designed, structuring each season into three training stages which were further subdivided into three training blocks or mesocycles (Accumulation, Transmutation and Realization), where the physical conditioning was focused on a minimal number of physical capacities. To examine training workloads, time spent developing each physical capacity was compared within blocks. To assess team performance in competition, the percentage of points obtained by the team in each match (points obtained/points in play; 3 points per victory, 1 point per draw; 0 points per defeat) was examined in relation to the training block. Time employed developing high-intensity aerobic (P<0.001) and gym-based strength (P<0.05) was higher in Accumulation, speed endurance (P<0.05) in Transmutation, and speed (P<0.05) in Realization. The highest success percentage in competition was achieved during Realization blocks (X2(2)=6.23; P<0.05), where the team obtained 59% of the points in play. The results of this study show that block periodization can be an alternative training design for professional soccer teams. Competitive team performance was greater during Realization blocks.